Renal Infarction Caused by Isolated Spontaneous Renal Artery Intramural Hematoma - Park, Sihyung (Am J Case Rep, 2015)
Patient: Male, 46 Final Diagnosis: Renal infarction Symptoms: Flank pain Medication: — Clinical Procedure: CT Specialty: Nephrology OBJECTIVE: Rare disease BACKGROUND: Acute renal infarction is an uncommon condition resulting from an obstruction or a decrease in renal arterial blood flow. Isolated spontaneous renal artery intramural hematoma is a rare cause of renal infarction. CASE REPORT: A 46-year-old healthy man presented to our emergency room because of sudden onset of severe right flank pain. An enhanced abdominal computed tomography scan showed a low-attenuated lesion in the lateral portion of the right kidney but no visible thromboembolisms in the main vessels. Computed tomography angiography revealed acute infarction resulting from intramural hematoma of the anterior segmental artery of the right kidney, with distal occlusion. CONCLUSIONS: The rarity and non-specific clinical presentation of renal infarction often lead to a delayed diagnosis that may result in impaired renal function. Clinical suspicion is important in the early diagnosis, and intramural hematoma of the renal artery should be considered the cause of renal infarction even in healthy patients without pre-disposing factors.